Crime and agricultural production: Reflections on Public Safety Risk, Productivity and transient crops rotation in a rural region of Colombia (Revista Iberoamericana de Estudios Municipales, 2024)
Given the situation of structural conflict in the country, the termed “public risk factor” in the Colombian countryside requires studies and applied methodologies for its evaluation and knowledge. The present research aims to present an analysis of the relationship between agricultural productivity of transitional crops and the typology of crimes during the period 2010-2015 in the 210 municipalities that make up the departments of Boyaca and Cundinamarca. As it was not possible to have a collection of information that is disaggregated from the geographical point of view, the databases of the Ministry of Agriculture of Colombia and the Ministry of National Defense (division of the criminal investigation and INTERPOL (International Criminal Police Organization) by applying classical linear regression in order to assess through an econometric model based on the relationship of crime typology and other variables directly related to agricultural production. The model shows low significance in trade theft, personal injuries and cell theft may not have an indirect impact in agricultural production for the studied region.
Keywords: Crime; typology; crops; harvesting; productivity; public risk